Pengaruh Teknik Relaksasi Nafas dalam terhadap Intensitas Nyeri Pasca Operasi di Ruang Bedah RSUD Hamba Muara Bulian Kabupaten Batanghari - Suharti Suharti; Maulani Maulani; Ani Astuti (STIKes Ibnu Sina Ajibarang, 2025)
Background: Postoperative pain is a common physiological response that can negatively affect the patient’s healing process. Deep breathing relaxation is a non-pharmacological method proven effective in reducing pain. Objective: To determine the effect of deep breathing relaxation technique on postoperative pain intensity in the Surgical Room of RSUD Hamba Muara Bulian. Methods: This study used a quasi-experimental design with a one-group pretest-posttest design involving 28 respondents. Data were analyzed using paired t-test to assess pain intensity differences before and after the intervention. Results: The mean pain intensity before the intervention was 5.36 (moderate category), which decreased to 2.89 (mild category) after the intervention. Statistical analysis showed a significant result with a p-value of 0.000. Conclusion: Deep breathing relaxation is effective in reducing postoperative pain intensity. It is recommended for implementation as a non-pharmacological intervention in surgical care settings.